2012
DOI: 10.1155/2012/819350
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Graphene Nanosheets and Manganese Valency on Lithium Storage Characteristics in Graphene/Manganese Oxide Hybrid Anode

Abstract: Graphene nanosheets (GNS) with attached MnOx nanoparticles are studied in regard to their structure and morphology. The relationship between the lithium storage performances and GNS contents as well as manganese valency was investigated. Experimental results showed that the specimen with 44 wt% GNS and high content of MnO delivered high reversible capacity (over twice of that in graphitic carbon anode), good cycling stability (0.8% fading per cycle), and high rate capability (67% at the 800 mA/g), which are dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…As shown in Figure 5d, EG/MnO shows good cyclability even at current density of 600 mA g −1 that is equivalent to theoretical capacity (with the respective amounts in the composite as anticipated from TGA weight percentages). Thus, the reversible capacities exhibited by EG/MnO are superior in comparison to that of MnO, 16,22 MnO/C, 6,7 and graphene/MnO 3,4,11,[13][14][15][16][17]24 (Table 1) composites. The overall electrochemical performance of EG/MnO is similar to the different MnO/C and graphene/ MnO composites cited in this study.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As shown in Figure 5d, EG/MnO shows good cyclability even at current density of 600 mA g −1 that is equivalent to theoretical capacity (with the respective amounts in the composite as anticipated from TGA weight percentages). Thus, the reversible capacities exhibited by EG/MnO are superior in comparison to that of MnO, 16,22 MnO/C, 6,7 and graphene/MnO 3,4,11,[13][14][15][16][17]24 (Table 1) composites. The overall electrochemical performance of EG/MnO is similar to the different MnO/C and graphene/ MnO composites cited in this study.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Various transition metal oxides (MO), such as M = Fe, Co, Ni, Cu, Mn, etc., are known to play an important role as anodes in lithium-ion batteries (LIB) because of their conversion reaction with Li (2Li + MO ↔ Li 2 O + M). Among the above-mentioned MO, MnO shows high theoretical capacity of 755 mAh g –1 (which is more than twice the capacity of carbonaceous materials) and low discharge–charge potential (around 0.5−1.2 V vs Li/Li + ). Moreover, it is a low-cost material, naturally abundant, and ecofriendly. , However, drawbacks such as low electronic conductivity and rapid capacity fading are observed in MnO electrodes owing to pulverization which is a consequence of volume changes upon lithiation and delithiation processes. ,, In order to overcome these drawbacks and improve the cyclic performance of MnO anodes, effective approaches like reduction in particle size, coating carbon onto MnO, ,,, and anchoring MnO onto graphene ,,, are studied.…”
Section: Introductionmentioning
confidence: 99%
“…[333][334] The electrochemical studies revealed that the valence state of manganese oxide significantly influences the lithium storage capacity of the manganese-oxide/graphene hybrid material. [335][336][337][338][339][340] Cheekati et al 335 reported that the MnO/graphene hybrid electrode has better storage and cycling stability than the Mn 3 O 4 /graphene hybrid electrode. Lee et al 341 synthesized graphene-MnO hybrid via spray pyrolysis method using the colloidal solution of GO and manganese nitrate hexahydrate.…”
Section: Manganese Oxide/graphene Hybridmentioning
confidence: 99%
“…The MGO/S composite powders were prepared by mechanically milling the mixture of rGO and S (Aldrich) for 15 minutes with an agate mortar and pestle. The rGO nanosheets were fabricated using the modified Hummer's method, which has been described elsewhere [37][38][39]. The S content in the MGO/S was tuned in the range of 20-70 wt%.…”
Section: Fabrication Of Go/s Compositesmentioning
confidence: 99%